2014
DOI: 10.1108/h-05-2012-0010
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic model of Ibn Khaldun theory on poverty

Abstract: Purpose – The purpose of this study is to examine the poverty rate of Indonesia, Malaysia and Pakistan representing majority Muslim populations and that of India as a minority Muslim population according to Ibn Khaldun's dynamic model on poverty. Design/methodology/approach – According to Ibn Khaldun, poverty is not merely influenced by economic dimensions. He initiated fundamental factors, as mentioned in his formula, which are the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Fiscal transfers from the central government to the local governments greatly affect local budget structures, especially for regions that do not have many natural resources (Alisjahbana, 2000;Affandi and Astuti, 2014). Increased allocation of transfers is followed by higher spending on regional budgets.…”
Section: Conceptual Framework and Research Hypothesismentioning
confidence: 99%
“…Fiscal transfers from the central government to the local governments greatly affect local budget structures, especially for regions that do not have many natural resources (Alisjahbana, 2000;Affandi and Astuti, 2014). Increased allocation of transfers is followed by higher spending on regional budgets.…”
Section: Conceptual Framework and Research Hypothesismentioning
confidence: 99%
“…Rambe & Purmini (2020), Mehmood & Sadiq (2010), Tsai & Huang (2007) stated that government spending plays a role in reducing poverty rates. Furthermore, several studies also reveal the role of government spending based on certain functions, such as infrastructure (Sasmal & Sasmal, 2016), social (Gomo, 2019;Yusuf, 2018;Celikay & Gumus, 2017;Fording & Berry, 2007;), and education and health (Affandi & Astuti, 2014). Based on this empirical research, government spending in this study refers to the activities in poverty initiated by the local government to alleviate economic, education, health, and social protection functions.…”
Section: Introductionmentioning
confidence: 96%
“…Rambe and Purmini (2020) analyzed poverty in Indonesia using the Sumatra province, which Syamsuri & Bandiyono, 2018;Tsai & Huang, 2007). Affandi & Astuti (2014) stated that government spending does not significantly affect poverty. Their role in reducing poverty can also be seen in implementing the expansion of districts/cities.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that if all these obstacles were addressed, alassabiyah can be the key for all the nation's distress (Halim, Ibrahim and Hamid, 2012). Affandi and Astuti (2014) conducted a study to test the challenges that might face the application of the Ibn-khaldun model of social change. In their study, the researchers tried to examine the poverty rates in Indonesia, Malaysia and Pakistan in which the majority of the Muslim population can be found, and India as a minority of the Muslim population.…”
Section: The Role Of Human Factors In the Social Change According To Ibn-khaldunmentioning
confidence: 99%